A study of serum uric acid levels in patients with ischaemic stroke and its relation with hypertension and diabetes mellitus in a tertiary hospital in Goa: a cross-sectional study - Kurdikar, Samidha Utkarsh; Rukma Kolwalkar; Abhishek Bicholkar (International Journal of Research in Medical Sciences, 2023)
Background: Stroke is second leading cause of mortality worldwide1 and fifth leading cause of disability-adjusted life years in India. Multiple studies show relationship of serum uric acid levels to prognosis of cardiovascular and cerebrovascular diseases. The present study aims to ascertain relationship of serum uric acid levels with ischaemic stroke and its co-morbidities, hypertension and diabetes mellitus. Methods: The present cross-sectional study was conducted in a tertiary care hospital in Goa. 100 admitted patients with ischaemic stroke meeting the inclusion criteria were enrolled for the study. Patients were evaluated for hyperuricemia, hypertension and diabetes mellitus. The unpaired student’s t test was used for assessing association. Results: A total of 100 patients were studied during the study period of 18 months. The mean age among males was 60.92±11.49 years and among females was 70.55±12.03 years. The mean serum uric acid levels in the patients with ischaemic stroke was 6.04±1.09 mg/dl which was significantly higher in male patients. There was a significant association between the mean serum uric acid levels and hypertension and diabetes among these patients. Conclusions: Serum uric acid levels could be of value in identifying patients at risk of ischaemic stroke especially those with comorbidities such as diabetes and hypertension. Judiciously selecting drugs, which could produce a hypouricemic effect may play a role in preventing ischaemic stroke in such patients. Further prospective studies are needed to establish the role of serum uric acid in ischaemic stroke.